Comparing the effect of body wash with marshmallow plant and lukewarm water on reducing the temperature of febrile children: a randomized clinical trial - Hadis Goodarzi; Fatemeh Valizadeh; Fatemeh Ghasemi; Farzad Ebrahimzade; Seyedeh Hanieh Seifosadat; Bahram Delfan; Nadereh Taee (BMC, 2022)
Abstract Background Fever is the most common reason for children's visits to medical centers. Its management is an essential duty of a pediatric nurse. The aim of this study was to determine the effect of body wash with Marshmallow plant on children's fever. Methods This parallel clinical trial was performed on 92 children aged 6 months to 10 years with a tympanic temperature above 38.3 °C. Participants were randomly assigned to groups. Simultaneously with receiving acetaminophen, body wash was performed in the control group with lukewarm water and in the intervention group with white Marshmallow extract. The children's temperature; from the beginning of the study was checked and recorded every 15 min in the first hour and in the 4th and 6th hours. The time duration to resolve fever, the frequency of afebrile children at different times of the study, and the value of temperature reduction were primary outcomes. Heart rate, the need to administer the next dose of acetaminophen, and the time of fever recurrence were recorded as secondary outcomes. Results The mean time duration to resolve fever in the intervention group was shorter than in the control group (B = 8.181, 95% CI 3.778-12.584, p < 0.001). The frequency of the children without fever was higher in the intervention group during different times of the study (p < 0.001). The mean value of temperature reduction in the intervention group was higher than the control group (B = -0.27 °C, 95% CI: -0.347 to -0.193, P < 0.001), although, after adjusting the effect of confounding variables it was not significant (P = 0.127). The mean of adjusted heart rate change (p = 0.771), the time of fever recurrence (P = 0.397), and the frequency of children requiring the next dose of acetaminophen (p = 0.397) did not show a significant difference between the groups. Conclusion Body wash with Marshmallow extract reduced children's fever in a shorter period of time and to some extent a greater extent than the control group without side effects. Therefore, it can be used as an effective and safe complementary method to help reduce fever. However, more studies are necessary for this field. Trial registration Registration in Iranian Clinical Trials (RCTs) on 31.08.2020 with registration code: IRCT20200809048345N1.